2023
DOI: 10.1039/d2py01593e
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric 3D printable base-detectors exploiting halocromic core-substituted naphthalenediimides

Abstract: 3D printing field is in rapid evolution, and its applications are widening continuously. Among the different techniques available, light induced vat-methods demonstrated to be particularly suitable for developing functional devices...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Among all these technologies, vat-photopolymerization (VP) 3D printing, which encompasses SLA and also digital light processing (DLP), are particularly interesting, since those are well-known for being the most flexible techniques to produce functional devices. In fact, in VP is possible to control the functionality both working on the design and on the composition of the printable formulations. , Furthermore, these techniques are characterized by very high resolution as well as the possibility to print multimaterial structures. , Among the vat-polymerization 3D printing technology, DLP offers the further advantage of higher printing velocity compared to SLA, since a complete layer of material is cured at the same time …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all these technologies, vat-photopolymerization (VP) 3D printing, which encompasses SLA and also digital light processing (DLP), are particularly interesting, since those are well-known for being the most flexible techniques to produce functional devices. In fact, in VP is possible to control the functionality both working on the design and on the composition of the printable formulations. , Furthermore, these techniques are characterized by very high resolution as well as the possibility to print multimaterial structures. , Among the vat-polymerization 3D printing technology, DLP offers the further advantage of higher printing velocity compared to SLA, since a complete layer of material is cured at the same time …”
Section: Introductionmentioning
confidence: 99%
“…28,29 Furthermore, these techniques are characterized by very high resolution 30 as well as the possibility to print multimaterial structures. 31,32 Among the vat-polymerization 3D printing technology, DLP offers the further advantage of higher printing velocity compared to SLA, since a complete layer of material is cured at the same time. 33 To the best of our knowledge, only Yoon et al 34 reported of a device partially fabricated with DLP able to harvest mechanical energy, employing photocurable resins mixed with PTFE powders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14–16 Starting from their computer-aided design (CAD) customized fabrication, 3D printing techniques are commonly more cost-efficient and faster than traditional manufacturing technologies. 17,18 These technologies can be divided into two main categories: extrusion-based and lithography-based 3D printers. 19 While extrusion-based technologies are known for their enhanced versatility ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Starting from their computer-aided design (CAD) customized fabrication, 3D printing techniques are commonly more costefficient and faster than traditional manufacturing technologies. 17,18 These technologies can be divided into two main categories: extrusion-based and lithography-based 3D printers. 19 While extrusion-based technologies are known for their enhanced versatility (e.g., fused direct ink writing and fused deposition modeling printers), lithography-based techniques permit the creation of complex and interconnected architectures with the best resolution overall.…”
Section: Introductionmentioning
confidence: 99%